2000
DOI: 10.1021/jp993733i
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of the Microsolvation of the Bromide Anion in Water, Methanol, and Acetonitrile:  Ion−Solvent vs Solvent−Solvent Interactions

Abstract: In this paper a theoretical study of the bromide solvation in three different polar solvents is presented:  water, methanol, and acetonitrile. DFT (B3LYP) calculations on the structure and energetics of [Br(Solv) n ]- clusters, for n = 1−9 and Solv = H2O, CH3OH, and CH3CN, have been carried out. Different structures where the anion is placed inside or on the surface of the cluster have been explored. The relative importance of solvent−solvent vs ion−solvent interactions determines the geometrical distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
2
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 65 publications
1
55
2
1
Order By: Relevance
“…The geometries of trimers and tetramers were taken from a previous quantum-mechanical work 68 concerning the microsolvation of the bromide anion. They present water molecular geometries distorted by the presence of the ion.…”
Section: B Quantum-mechanical Calculationsmentioning
confidence: 99%
See 3 more Smart Citations
“…The geometries of trimers and tetramers were taken from a previous quantum-mechanical work 68 concerning the microsolvation of the bromide anion. They present water molecular geometries distorted by the presence of the ion.…”
Section: B Quantum-mechanical Calculationsmentioning
confidence: 99%
“…87 Nevertheless, the influence of these small variations on the results of the Monte Carlo simulations and numerical minimizations is not clear, so we will proceed to check it. In a previous work 68 dealing with the microsolvation of the bromide ion in different solvents, a…”
Section: Fitting Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…104 Furthermore, the previous experimental and theoretical studies have shown that 9-11 CH 3 CN molecules can nearly complete the first solvation layer for halide ions. 31,116 In the first solvation layer, the strong direct ion (or excess electron)-solvent interaction results in efficient anion (or excess electron) stabilization. In contrast, in the second (and larger) layer(s), solvent molecules do not directly interact with the core charge and hence provide no further substantial stabilization for the anion or excess electron.…”
Section: Research Backgroundmentioning
confidence: 99%